Factors Affecting Purchasing Decision To Buying Capital Stock Using Of Provincial Electricity Authoriry’s Employess Saving - พงศ์พัฒน์ ฑิฆัมพร; ชั้วเจริญ อรไท (Business Administration and Management Journal Review, 2020)
The purposes of this research were to study the affecting the capital stock decision and to study the factors the decision to buying capital stock using of Provincial Electricity Authority’s Employees. The sample was 400 people. Data was collected by simple multi-stage sampling through questionnaires. The statistical analysis methods are percentage, mean, standard deviation, and chi-square were applied as statistical analysis tools. The results presented the majority of sample is female of female age between 31 to 40 years old, holding Bachelor degree, single, they have had to support 1 to 2 people in their families. They had joined the member of the co-operative for 1 to 5 years. They had a monthly income 10,001 to 30,000 Thai baths and monthly expenses 10,001 to 30,000 Thai baths. The revenue and expenditure were balance and nature of expenditure which resulted in debt is to buy houses. They bought capital stock for saving with budget 1,000 to 3,000 Thai baths per month. The majority of the respondents had attitude toward Image of cooperative, Impression in service and advantage of good dividend. In the level of the level was high. Hypothesis testing showed that 1) Different personal factors when they made decision to buy the capital stock. 2) Income and expenses resulted in differences of capital stock purchasing decision. 3) Image of cooperative, Service and Dividend payment. Statistical significance levels were set at 0.05.